The nest architecture of stingless bees with special reference to those of Costa Rica (Hymenoptera, Apidae) - Wille, Alvaro; Michener, Charles D. (Revista de Biología Tropical, 1973)
The purpose of this work is to provide comparative information on the nest sites and architecture of the whole apid tribe Meliponini as well as data on the hitherto undescribed nests of certain species from Costa Rica. The field work involved opening limited numbers of nests of as many species as possible and recording the nest structure and organization by means of notes, diagrams, and photographs. We have not attempted the detailed kind of examination of architecture such as Nogueira-Neto's (40) study of cells, for such investigations are best done with colonies in hives. Qur interest has been in the field conditions and architectural adaptations to various kinds of cavities. The stingless bees are the most common bees and possibly the most important pollinators in the American tropics. They are less numerous in the African, Asiatic and Australian tropics but nonetheless are a significant element of the fauna, especially in the Malayan area. They are also sources of minor quantities of honey and wax. In addition to their major positive value as pollinators, sorne of them are significant pests. Various species cut leaves, buds, and bark of young trees, causing significant lesses to agriculture and horticulture, and transmit certain plant diseases.